Fabrication of a "turn-on"-type enantioselective fluorescence sensor via a modified achiral MOF: applications for synchronous detection of phenylalaninol enantiomers. Issue 3 (26th November 2020) - Xiao, Jiannan; Wang, Xueling; Xu, Xuebin; Tian, Fuli; Liu, Zhiliang
Abstract : One pair of homochiral UiO-66 analogues, S -1 and R -1, can detect enantiomeric PA with different ef values and a distinct enantioselectivity factor α . Abstract : Homochiral metal–organic frameworks (HMOFs) have garnered considerable attention due to their extrachiral properties and broad application for chiral recognition. However, assembling a pair of high-quality chiral MOFs for sensing enantiomers precisely is a formidable challenge because of the complicated chiral environment and uncontrollable coordinated conditions. Herein, one pair of homochiral UiO-66 analogues, S -1 (l -AP@UiO-66-(COOH)2 ) and R -1 (d -AP@UiO-66-(COOH)2 ), are reported for chiral recognition. They were fabricated via a condensation reaction between the carboxyl groups of UiO-66-(COOH)2 and amino groups of l /d -amino propanol (l /d -AP). These novel fluorescent probes exhibited highly enantioselective fluorescence enhancement towards l /d -phenylalaninol (l /d -PA). For example, when S -1 and R -1 were treated with l -PA or d -PA, they displayed different fluorescence responses: the enantiomeric fluorescence enhancement ratio (ef) was 2.51 and 0.41 for S -1 and R -1, respectively. Hence, a visible difference in fluorescence enhancement for l -PA and d -PA and excellent enantioselective behavior between S -1 and l -PA (or R -1 and d -PA) was displayed. Measurements of fluorescence lifetime, powder X-ray diffraction, molecular-dynamic simulations and Benesi–Hildebrand plots were employed to determine the observed high enantioselectivity for l /d -PA. In brief, we found that two post-modified HMOFs, S -1 and R -1, were outstanding enantioselective sensors for detecting l -PA and d -PA. They had a prominent difference in ef and remarkable enantioselectivity factor α and ΔΔ G based on steric hindrance and stereochemical difference.